The phosphorylation level of Cofilin-1 is related to the pathological subtypes of gastric cancer. Issue 43 (28th October 2022) - Kang, Xi; Zhao, Chunfang; Liu, Yueping; Wang, Guiying
Abstract : The purpose of the study was to explore the relationship between multiple proteins belonging to the LIMK/Cofilin pathway, including LIMK1, LIMK2, Cofilin-1, and p-Cofilin-1 and clinical features of gastric cancer (GC) patients, including overall survival, TNM stages, and pathological subtypes. The expression of LIMK1, LIMK2, Cofilin-1 and p-Cofilin-1 in the GC tissues and adjacent normal stomach tissues from 141 patients were detected using immunohistochemistry (IHC) staining. Wilcoxon rank-sum test and Spearman rank correlation coefficients were used to measure the relationship between different TNM stages, pathological types, and selected parameters. OS was estimated using the Kaplan–Meier method and survival curves were compared using the log-rank test. Our results showed that, compared to those in the adjacent normal stomach tissues, LIMK1, LIMK2 and Cofilin-1 were up-regulated while p-Cofilin-1 was down-regulated in the GC tissues. LIMK1 level was positively correlated to the TNM stages of GC. According to the published dataset, the expression levels of both LIMK1 and LIMK2 were correlated to the overall survival time of GC patients. The level of Cofilin-1 was significantly different between GCs of different TNM stages. Moreover, most importantly, this is the first study to reveal that the level of Cofilin-1 is higher, and the level of p-Cofilin-1 is lower in the diffuse type of GC compared to that in intestinal type. Taken together, our study demonstrated that multiple factors in LIMK/Cofilin pathway including LIMK1, LIMK2, Cofilin-1, and p-Cofilin-1 were associated with the clinical and pathological features of GC, which is potentially helpful for the diagnosis and treatment of GC.